Characterization of biomechanical properties of aged human and ovine mitral valve chordae tendineae. (September 2016) - Zuo, Keping; Pham, Thuy; Li, Kewei; Martin, Caitlin; He, Zhaoming; Sun, Wei
Abstract: The mitral valve (MV) is a highly complex cardiac valve consisting of an annulus, anterior and posterior leaflets, chordae tendineae (chords) and two papillary muscles. The chordae tendineae mechanics play a pivotal role in proper MV function: the chords help maintain proper leaflet coaptation and rupture of the chordae tendineae due to disease or aging can lead to mitral valve insufficiency. Therefore, the aim of this study was to characterize the mechanical properties of aged human and ovine mitral chordae tendineae. The human and ovine chordal specimens were categorized by insertion location (i.e., marginal, basal and strut) and leaflet type (i.e., anterior and posterior). The results show that human and ovine chords of differing types vary largely in size but do not have significantly different elastic and failure properties. The excess fibrous tissue layers surrounding the central core of human chords added thickness to the chords but did not contribute to the overall strength of the chords. In general, the thinner marginal chords were stiffer than the thicker basal and strut chords, and the anterior chords were stiffer and weaker than the posterior chords. The human chords of all types were significantly stiffer than the corresponding ovine chords and exhibited much lower failure strains. These findings can be explained by the diminished crimp pattern of collagen fibers of the human mitral chords observed histologically. Moreover, the mechanical testing data was modeled with the nonlinear hyperelastic Ogden strain energy function to facilitate accurate computational modeling of the human MV.